2011
DOI: 10.3109/0886022x.2010.541577
|View full text |Cite
|
Sign up to set email alerts
|

A Patient with Crohn's Disease who Presented with Thrombotic Thrombocytopenic Purpura/Hemolytic Uremic Syndrome

Abstract: Thrombotic thrombocytopenic purpura (TTP)/hemolytic uremic syndrome (HUS) is characterized with fever, purpura, anemia due to microangiopathic hemolysis, thrombocytopenia, kidney damage, and neurologic symptoms. The development of TTP/HUS during the course of inflammatory bowel diseases was rarely reported. However, coexistence of TTP/HUS and Crohn's disease in the same patient has not been reported previously. We herein present a case of TTP/HUS who presented with Crohn's disease. He responded to cyclosporine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
2
1
Order By: Relevance
“…Autoimmune thrombocytopaenia overlapping CD is not frequent,8 but it has been reported both in CD and in anti-TNFa-treated patients with CD 9. In this subject, however, we observed absence of antiplatelet autoantibodies and peripheral schistocytosis, which was more suggestive of TMA; lupus-like syndromes can overlap CD or be induced by anti-TNFa treatment but were excluded by absence of antinuclear antibodies; secondary forms due to malignancy, particularly lymphoma, were ruled out by instrumental tests; few cases of TMA have been described in CD 10. Often, these cases are described as autoimmune, mimicking thrombotic thrombocytopaenic purpura11 with an autoimmune mechanism.…”
Section: Differential Diagnosiscontrasting
confidence: 49%
“…Autoimmune thrombocytopaenia overlapping CD is not frequent,8 but it has been reported both in CD and in anti-TNFa-treated patients with CD 9. In this subject, however, we observed absence of antiplatelet autoantibodies and peripheral schistocytosis, which was more suggestive of TMA; lupus-like syndromes can overlap CD or be induced by anti-TNFa treatment but were excluded by absence of antinuclear antibodies; secondary forms due to malignancy, particularly lymphoma, were ruled out by instrumental tests; few cases of TMA have been described in CD 10. Often, these cases are described as autoimmune, mimicking thrombotic thrombocytopaenic purpura11 with an autoimmune mechanism.…”
Section: Differential Diagnosiscontrasting
confidence: 49%
“…We read with great interest the contribution by Unverdi et al 1 They reported a case of thrombotic thrombocytopenic purpura (TTP)/hemolytic uremic syndrome (HUS) that presented with Crohn's disease (CD) and presumed microthrombosis triggered by autoimmune disorders to be the main cause in the development of TTP/HUS and CD. The first report of HUS in patients with CD also described thrombosis at the microvascular level and increased coagulability as an important mechanism involved in the two diseases.…”
Section: Letter To the Editormentioning
confidence: 95%
“…Less well described is an association between inflammatory bowel disease (IBD) and aHUS. There have been only six cases of HUS associated with IBD reported in the literature, nearly all of which were in adult patients [8, 9, 10, 11, 12]. We evaluated the genetic background of three cases of pediatric patients with co-existing aHUS and IBD to determine if there was a genetic predisposition of their aHUS and whether there were any correlations between aHUS and IBD.…”
Section: Introductionmentioning
confidence: 99%